Lean Service and BPM to Increase the Efficiency of an Operational Process in the Insurance Sector - Jacinto, Mariela (2022)
One of the pillars of the world economy is the service sector, since in developed and developing countries it contributes 70% and 45% of GDP, respectively. For this reason, companies in this sector seek to innovate their processes, become more efficient and competitive. In this sense, Lean Service and BPM stand out for generating efficiency and competitiveness in Back Office processes, through a focus on optimizing the value of processes, eliminating activities and reducing waste. In this case study, the aim is to increase the efficiency of the process of issuing electronic receipts in a Peruvian Banking and Insurance company, through the implementation of Lean and BPM tools such as: electronic 5s, digital Poka Yoke, load balancing and BPMN. Our proposal model includes the aforementioned Lean Service and BPM tools, which together achieve the reduction of rework, reduction of time in operation and reduction of overtime, which translates into increased process efficiency. Although more and more companies are applying Lean tools in the Services sector, there are still few precedents for their application in the Banking and Insurance sector. In this sense, the novelty of our proposal is the application of a model that combines Lean and BPM tools, such as Poka Yoke and electronic 5s in a digital work environment, obtaining favorable results. For this reason, this research will contribute to the scientific community a new model to increase efficiency in companies in the insurance sector in Latin America.